PENENTUAN HARGA POKOK PRODUKSI KERUPUK JANGEK JALAN KARTINI DUMAI - Melliana, Melliana; Simanullang, Sanco; Azmi, Azmi; Fitra, Fitra; Mesra, Trisna (Komunitas Manajemen Kompetitif, 2024)
The jangek cracker business is a community business that is still rarely carried out by the people of Dumai city. This business often experiences a decline in productivity because it experiences low profits or even no profits at all and only reaches the break even point. The rarity of this business stems from problems in determining the cost price incorrectly, thus determining the selling price too low. In accordance with the problems experienced by partners, the research team offers a solution by providing skills through training on how to prepare the cost of production and calculate the cost of production systematically and precisely. The expected goal is to create increased knowledge and skills in systematically preparing the cost of production so that it is appropriate to determine the selling price.